Possibilities of using telemedicine in developing countries on the example of Ghana and Kenya - Ewa Zieliński; Katarzyna Sas; Rafał Gotowski (Kazimierz Wielki University, 2018)
The paper addresses the problem of the lack of access to medical services and qualified medical staff in developing countries on the example of Kenya and Ghana. The paper presents possibilities of using telemedicine in Kenya and Ghana. It was proposed to appoint the function of a medical coordinator. The project of implementing telemedicine in Kenya was described and the possibility of implementing the system for Ghana was indicated. The benefits of using telemedicine for both medical personnel and the patient are presented.